2015
DOI: 10.1161/jaha.115.001820
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated With QT Prolongation in the General Population

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is independently associated with QT prolongation among patients with diabetes. It has not yet been determined whether this association remains valid in the general population. We designed an observational study to explore this association.Methods and ResultsWe conducted a cross-sectional analysis of 31 116 consecutive participants in our health management program. Heart rate–corrected QT (QTc) interval was derived from 12-lead electrocardiography and by Bazett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 41 publications
6
73
0
1
Order By: Relevance
“…However, it is important to emphasize that the association between NAFLD and ventricular arrhythmias remained significant in our study even after adjusting for many cardiometabolic risk factors, LV ejection fraction, preexisting IHD, and comorbid conditions. This finding corroborates previous observations reporting a strong association between NAFLD and an increased risk of QTc interval prolongation, which is a powerful risk factor for ventricular arrhythmias (8,9). In particular, we recently demonstrated that NAFLD was associated with an increased QTc interval among patients with type 2 diabetes without known liver diseases, and this association remained significant after adjusting for age, sex, hypertension, diabetes-related variables, LV hypertrophy, and comorbid conditions (8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, it is important to emphasize that the association between NAFLD and ventricular arrhythmias remained significant in our study even after adjusting for many cardiometabolic risk factors, LV ejection fraction, preexisting IHD, and comorbid conditions. This finding corroborates previous observations reporting a strong association between NAFLD and an increased risk of QTc interval prolongation, which is a powerful risk factor for ventricular arrhythmias (8,9). In particular, we recently demonstrated that NAFLD was associated with an increased QTc interval among patients with type 2 diabetes without known liver diseases, and this association remained significant after adjusting for age, sex, hypertension, diabetes-related variables, LV hypertrophy, and comorbid conditions (8).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, we recently demonstrated that NAFLD was associated with an increased QTc interval among patients with type 2 diabetes without known liver diseases, and this association remained significant after adjusting for age, sex, hypertension, diabetes-related variables, LV hypertrophy, and comorbid conditions (8). Similarly, Hung et al (9) reported that the ultrasonographic severity of NAFLD was associated with a higher risk for QTc interval prolongation in a large populationbased study, independently of age, sex, hypertension, diabetes, total cholesterol, eGFR, BMI, LV hypertrophy, history of IHD, or hypokalemia.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This increased epicardial adipose tissue is associated with sympathovagal imbalances that can predispose to cardiac arrhythmias, such as first degree heart block prolongation and atrial fibrillation. [106][107][108][109][110][111] A prospective cohort study following diabetic patients for 10 years showed that patients with NAFLD developed atrial fibrillation more often than the controls. 112 These findings suggest a potential role for screening and surveillance of atherogenic dyslipidemia in patients with NAFLD.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In a recent study, Hung et al 27 investigated whether the association between NAFLD and QTc interval prolongation also exists in the general adult population. In that study, the investigators reported that the severity of NAFLD was associated with a higher risk of QTc interval prolongation, even after adjustment for several cardiometabolic risk factors and other important comorbidities 27. Notably, such association was found to be present in all subgroups of patients analyzed, including patients with T2DM 27…”
Section: Nafld and Risk Of Ventricular Arrhythmiasmentioning
confidence: 99%